DESAIN DAN UJI UNJUK KERJA KINCIR ANGIN - Dalom, Dalom (Politeknik Negeri Sriwijaya, Indonesia, 2011)
Windmill power plant is one which is moved by wind energy, windmill designs developed in this test using a blade from PVC material with a diameter of 2.2 m span turbines as power using car alternator DC 12 Volt, Round the mill also depends on the speed of the wind flow , the faster the flow of wind so the sooner the revolution generated turbines. alternator used as wind power, with the average voltage is removed the alternator produces a voltage of 2.096 volts